Pengembangan Media Pembelajaran Lift the Flap Book Tangga Nada Peserta Didik Kelas V Sekolah Dasar - Akhmad Akbar Harmila; Rintis Rizkia Pangestika; Muflikhul Khaq (Perkumpulan Kualitama Edukatika Indonesia, 2021)
The research focuses on developing the lift the flap book learning media as a companion in SBdP learning on scale material. This study aims to describe product development in the form of lift the flap book media on scale material and determine the feasibility of lift the flap book media on scale material for Class V Elementary School 2 Mlaran. The method used in this research is development research (R&D). This study uses the Four-D (4D) development research model. This research includes four steps, namely define, design, develop, and disseminate. The test subjects in this study were fifth grade students at SDN 2 Mlaran. The results of the assessment by material experts were 86.5% in the very good category, the assessment by media experts was 88.3% in the very good category. The results of the implementation of the first stage of learning were 92.7% and the second stage was 95.3%. The results of the response of the first stage students were 90% and the second stage was 87.7%. Thus, the learning media for the lift the flap book scales is appropriate to be used as a learning medium for the fifth grade of elementary school.